السمات التربوية في القصص القرآني وأثرها في التدريس - Garba, Ahmad (SIBAWAYH Arabic Language and Education, 2025)
المخلص لا يخفى على أحدٍ أنَّ القصصَ في التراثِ الإنسانيِّ تلعبُ دورًا كبيرًا في نقلِ الخبراتِ والدروسِ في التوجيهِ والتربية، وذلك لما للقصةِ من أثرٍ عميقٍ في نفسِ المتلقّي وتكوينه وتشكيلِ وعيه، ومن الملاحظِ أنَّ العِبرةَ والموعظةَ المجرّدةَ لا تؤثّرُ في الفردِ وتجعله يطيعُ ويستجيبُ إلّا إذا اقترنت بقصّةٍ واقعيةٍ. لذلك نجدُ أنَّ القرآنَ الكريمَ اهتمَّ بالقصةِ اهتمامًا كبيرًا، وتنوّعَ في سردِها وعرضِها، وأبدعَ في أسلوبِه، واعتمدَ على تقديمِ العِظةِ والعِبرةِ في صورةِ قصّةٍ لتكونَ أكثرَ فاعليةً وأكبرَ أثرًا في التربيةِ والتذكير. إنَّ قصصَ القرآنِ ميدانٌ خصبٌ للدعوةِ والتربية، وفيها من العِبرِ والمواعظِ والحِكمِ ما ينتفعُ به المربّون، وينتفعُ به المعلّمون، ويتزوّدُ الصالحونَ من مصدرِها. وعلى هذا الأساس يهدفُ هذا البحثُ إلى إلقاءِ الضوءِ على السماتِ التربويةِ في القصصِ القرآنيِّ وأثرِها في التعليم، ومدى مبرّراتِها في الاستجابةِ لرغباتِ المتعلّمين. وقد استخدمَ الباحثُ المنهجَ الوصفيَّ للحصولِ على المعلوماتِ المتعلّقةِ بالموضوع، وتوصّلت نتيجةُ الدراسةِ إلى أنَّ للقصةِ القرآنيةِ أثرًا إيجابيًّا في تحسينِ تحصيلِ المتعلّمين. الكلمات المفتاحية: القرآن الكريم، التعليم، التعلّم، الأهداف، الاستراتيجية. Abstract It is clearly open that stories in human heritage play a major role in conveying experience and lessons in guidance and education, due to the profound impact of stories on human’s soul, formation, and shaping of his awareness. It is seen that a lesson and abstract sermon do not affect the individual and make him obey and respond unless they are coupled with a real story.Therefore, Holy Qur’an paid great attention to the story, diversified its narration and presentation, and was creative in its style, and relied on presenting the sermon and lesson in the form of a story to be more effective and greater in education and reminder.The stories of the Qur’an are a fertile field for advocacy and education, and it contains lessons, and wisdom, from which teachers and students benefit. On this basis, this paper aims to shed light on the educational features of the Quranic narrative and its impact on teaching and learning, and the extent of its justification in responding to the desire of learners. The researcher used the descriptive design to obtain information related to the subject, and the result of the study concluded that the Quranic narrative has a positive impact on improving learners’ educational achievements. Keywords: Holy Quran, education, learning, goals, strategy.